2014
DOI: 10.1177/1938640014539810
|View full text |Cite
|
Sign up to set email alerts
|

Positive Drawer Test Combined With Radiographic Deviation of the Third Metatarsophalangeal Joint Suggests High Grade Tear of the Second Metatarsophalangeal Joint Plantar Plate

Abstract: Diagnostic, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…AP radiographs were analyzed for metatarsus adductus angle ( Figure 2), 9 first and second intermetatarsal angle (IMA), talocalcaneal angle, calcaneocuboid abduction angle, talo-first metatarsal angle, hallux valgus angle, and second and third MTP joint deviation angles (Figure 3). 15 Lateral radiographs were examined for calcaneal inclination angle, talar declination angle, first metatarsal declination angle, fifth metatarsal declination angle, talo-first metatarsal (Meary's) angle, Seiberg index, 24,25 and hallux equinus angle (Figures 4 and 5). 24 All measurements were performed as described by Thomas et al, 28 unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…AP radiographs were analyzed for metatarsus adductus angle ( Figure 2), 9 first and second intermetatarsal angle (IMA), talocalcaneal angle, calcaneocuboid abduction angle, talo-first metatarsal angle, hallux valgus angle, and second and third MTP joint deviation angles (Figure 3). 15 Lateral radiographs were examined for calcaneal inclination angle, talar declination angle, first metatarsal declination angle, fifth metatarsal declination angle, talo-first metatarsal (Meary's) angle, Seiberg index, 24,25 and hallux equinus angle (Figures 4 and 5). 24 All measurements were performed as described by Thomas et al, 28 unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered the most accurate clinical test for diagnosing second MTP joint pathology (sensitivity, 91.5%; specificity, 99.8%). 41,71 Magnetic resonance imaging (MRI) and ultrasound are appropriate modalities for imaging of the plantar plate. Ultrasound is a more sensitive exam (ultrasound sensitivity, 91.5%; MRI sensitivity, 73.9%), but MRI is a more specific exam (MRI specificity, 100%; ultrasound specificity, 25%).…”
Section: Case Description Historymentioning
confidence: 99%
“…2,11,28,33,48,66,69,79 It is the most commonly used generic tool in the orthopaedic literature 3 and is often considered the gold standard by which other foot and ankle outcome tools are measured. 13,45,67 The DFOS is a dance-specific lower extremity questionnaire developed upon finding ceiling effects and problems with validity when using region-specific and sport-specific measures on dancers. 10 The tool assesses a dancer's ability to accomplish activities of daily living or dance movements.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The authors showed a combination positive drawer test of second MTPJ and transverse deviation of the third MTPJ on plain films suggested an underlying high-grade plantar plate tear of the second MTPJ. 2,3 These studies also highlighted the need for advanced imaging to distinguish between high-and low-grade tears. Klein Anatomic Repair of Plantar Plate With Flexor Tendon Sheath Reinforcement static images to diagnose subtle injuries in the forefoot.…”
Section: Levels Of Evidence: Level V: Case Seriesmentioning
confidence: 97%